The association between verbal working memory, visual spatial working memory and executive functioning with functional outcomes in patients with schizophrenia / Sasitharan Moorthi - Sasitharan , Moorthi (2017)
Cognitive impairment in schizophrenia patients has been identified from the early description of the illness. Cognition plays an important role in recovery process of schizophrenia. Recovery has been the vision of treatment outcome in schizophrenia patients in this current era. Functionality among schizophrenia has been a major factor and determinant of recovery and success of rehabilitation programmes. The association between cognition and functionality is being actively studied globally. However, the connection between cognition and functionality is still very new and not explored in Malaysia.